Integration of Mathematics Contextual Values in PGSD Students' Picture Story Project - Prihastari, Ema Butsi; Rizkasari, Elinda; Novit, Trio Adi (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
This study aims to describe the integration of contextual values in mathematics teaching materials through a pictorial story project developed by PGSD students. This study uses a descriptive qualitative approach with the subject of 30 6th semester students who took the Mathematics Teaching Material Development course. Data were collected through observation of illustrated story products and semi-structured interviews. The results of observations showed that 76% of students' work showed a high integration of contextual values, such as honesty, responsibility, and cooperation, in the context of students' daily lives. In-depth interviews revealed that students were able to relate mathematical concepts to character values creatively, although some experienced difficulties in composing a narrative that was proportional to the material. The project also encourages students' pedagogic and reflective awareness of the importance of contextual education. These findings show that pictorial story media can be an innovative alternative in the development of mathematics teaching materials that are not only cognitive, but also affective. This study recommends strengthening value integration training in teaching media design as well as further implementation testing at the elementary school level.